(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
The effect of alcoholic extract of Chenopodium album Linn. (Chenopodiaceae) was investigated in rats to evaluate the anti-ulcer activity by using three models, i.e., pyloric ligation, ethanol and cold restraint stress induced ulcers. Ranitidine was used as reference standard. The parameters taken to assess anti-ulcer activity were volume of gastric secretion, pH, free acidity, total acidity and ulcer index. The results indicate that the alcoholic extract significantly decreases the volume of gastric acid secretion, free acidity, total acidity and ulcer index with respect to control. Sections of ulcerated area revealed that there was a significant increase in regenerated glandular epithelium width after treatment with the alcohol extract. The collagen content in the ulcerated tissue was significantly increased by alcohol extract and ranitidine, showing the maximum effect. No significant difference on capillary density in scar tissue was observed after treatment with alcohol extract or ranitidine.